2017
DOI: 10.1364/optica.4.001171
|View full text |Cite
|
Sign up to set email alerts
|

3D second harmonic generation imaging tomography by multi-view excitation

Abstract: Biological tissues have complex 3D collagen fiber architecture that cannot be fully visualized by conventional second harmonic generation (SHG) microscopy due to electric dipole considerations. We have developed a multi-view SHG imaging platform that successfully visualizes all orientations of collagen fibers. This is achieved by rotating tissues relative to the excitation laser plane of incidence, where the complete fibrillar structure is then visualized following registration and reconstruction. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In theory close to isotropic resolution can be achieved with only 4 views but for thicker samples not all details are captured equally in every view. In a study based on SHG signal MVI, it was shown that a intertwining collagen fibre was visualized more clearly using 10 views 17 , whereas for LSFM MVI up to 24 views might be necessary to capture all the details of a large sample and to overcome local distortion due to scattering and refraction within the sample 39 . Recently it was shown that for samples not clearly visible in all views selecting pixels rich in information can provide better results than blindly incorporating all views in the MVD 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory close to isotropic resolution can be achieved with only 4 views but for thicker samples not all details are captured equally in every view. In a study based on SHG signal MVI, it was shown that a intertwining collagen fibre was visualized more clearly using 10 views 17 , whereas for LSFM MVI up to 24 views might be necessary to capture all the details of a large sample and to overcome local distortion due to scattering and refraction within the sample 39 . Recently it was shown that for samples not clearly visible in all views selecting pixels rich in information can provide better results than blindly incorporating all views in the MVD 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite computational power being readily available, MVI, has not found many applications in scanning microscopy, such as MPM and confocal microscopy. Indeed, some applications in MPM have been demonstrated, based on the signal of Second Harmonic Generation (SHG) from collagen fibres 16 , 17 . However, MVD has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of perfect phase matching, i.e. where phase mismatch Δ = 0, emission propagates in the forward-scattered and back-scattered (FSHG, BSHG) directions 32,36,46 . Second harmonic signals, however, can be generated in other directions In the case of imperfect phase matching, where Δ ≠ 0 such as in biological tissues 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, SHG signals are directional rather than isotropic, like in fluorescence emission (1PF or 2PF). Existing 3D imaging approaches use a variety of mechanical or computational methods 39,[46][47][48] , but all generate data through point-scanning, and use only a forward-and/or backscattered detection geometry for SHG signal collection. Since LSM uses an orthogonal signal collection configuration instead of collinear excitation and detection, it presents a frontier for SHG imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Despite computational power being readily available, MVI, has not found many applications in scanning microscopy, such as TPLSM and confocal microscopy. Indeed, some applications in TPLSM have been demonstrated, based on the signal of Second Harmonic Generation (SHG) from collagen bres 13,14 .…”
Section: Introductionmentioning
confidence: 99%